2017
DOI: 10.4236/ojepi.2017.72009
|View full text |Cite
|
Sign up to set email alerts
|

Refining a Church-Based Lifestyle Intervention Targeting African-American Adults at Risk for Cardiometabolic Diseases: A Pilot Study

Abstract: Objective: The pilot study was intended to test the feasibility of a multiple-component lifestyle intervention targeting African American adults in a weight control and cardiometabolic risk reduction program on diet, activity, and stress, using community-engagement principles. Methods: Applying mixed qualitative and quantitative measures, the intervention had a two-part sequential study design consisting of 12 weekly small group sessions that provided individual and group counseling in nutrition, exercise, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 60 publications
0
4
0
Order By: Relevance
“…IMPACT: Participants in post-study focus groups reported that: (Brown et al, 2019;Zhou et al, 2017). Focus groups of AA church members following a small pilot study (The Biomedical/Obesity Reduction Trial) identified barriers to dietary change including flavor preferences, cost and time commitment to healthy eating, lack of knowledge regarding recipes or cooking methods, and maintaining motivation (Zhou et al, 2017). Only one study reported on post-study focus groups after a large, multisite diabetes prevention intervention, the Hosea Project (the Hosea Project; Brown et al, 2019).…”
Section: Impact Statementmentioning
confidence: 99%
See 2 more Smart Citations
“…IMPACT: Participants in post-study focus groups reported that: (Brown et al, 2019;Zhou et al, 2017). Focus groups of AA church members following a small pilot study (The Biomedical/Obesity Reduction Trial) identified barriers to dietary change including flavor preferences, cost and time commitment to healthy eating, lack of knowledge regarding recipes or cooking methods, and maintaining motivation (Zhou et al, 2017). Only one study reported on post-study focus groups after a large, multisite diabetes prevention intervention, the Hosea Project (the Hosea Project; Brown et al, 2019).…”
Section: Impact Statementmentioning
confidence: 99%
“…Elicitation of qualitative feedback may help address these impact and implementation issues in AA faith-based obesity prevention programs, including Project FIT. However, there are limited qualitative reports on feedback from participants who have engaged in faith-based obesity, physical activity, or dietary interventions to understand how to refine and improve such interventions (Brown et al, 2019; Zhou et al, 2017). Focus groups of AA church members following a small pilot study (The Biomedical/Obesity Reduction Trial) identified barriers to dietary change including flavor preferences, cost and time commitment to healthy eating, lack of knowledge regarding recipes or cooking methods, and maintaining motivation (Zhou et al, 2017).…”
Section: Refining Faith-based Diabetes Heart Disease and Stroke Preve...mentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, some other studies considered mindfulness, mindful eating, regular exercise, and eating behaviors [26]; reward-based eating [10]; anxiety and depressive symptoms [32]; fasting glucose and blood pressure [33]; depression, sleep quality, regular exercise, and healthy eating [27]; diabetes biomarkers, body measurements, personal satisfaction, diet, and activity measures [34]; barriers and facilitators of healthful eating behaviors, being active, and practicing mindfulness [28]; and depression [35].…”
Section: Selection Processmentioning
confidence: 99%
“…Underlying most of these conditions are modifiable lifestyle behaviors. Diet quality, 9,10 time spent in physical activity, 11 and stress-reduction 12,13 are all targeted for weight loss and prevention of obesity and obesity-related chronic diseases. While examinations of these health behaviors among clergy are limited, they indicate clergy have difficulty eating healthy, 1 spend little time in moderate-to-vigorous physical activity, 7,14 and report moderate to high levels of occupational stress.…”
Section: Purposementioning
confidence: 99%